1999
DOI: 10.1007/s004120050368
|View full text |Cite
|
Sign up to set email alerts
|

A novel histone variant localized in nucleoli of higher plant cells

Abstract: Immunofluorescence staining with antisera raised against p35, a basic nuclear protein that accumulates in the pollen nuclei of Lilium longiflorum, specifically stained the nucleoli in interphase nuclei of somatic tissues, including root and leaf, and in pachytene nuclei during meiotic division, whereas antisera raised against histone H1 uniformly stained the entire chromatin domain with the exception of the nucleoli in these nuclei. Further, p35-specific antisera stained the nucleoli in root and leaf nuclei of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 56 publications
1
11
0
1
Order By: Relevance
“…Histone H1x, a subtype located in chromatin regions not affected by micrococcus nuclease (25), is also located in the nucleolus region at G 1 phase (44). In plants a histone H1 variant called p35 is also enriched in the nucleolus (46). In yeast, it represses recombination at the ribosomal DNA locus (32).…”
mentioning
confidence: 99%
“…Histone H1x, a subtype located in chromatin regions not affected by micrococcus nuclease (25), is also located in the nucleolus region at G 1 phase (44). In plants a histone H1 variant called p35 is also enriched in the nucleolus (46). In yeast, it represses recombination at the ribosomal DNA locus (32).…”
mentioning
confidence: 99%
“…Some reports have shown that linker histone H1 were preferentially localized in the cell nucleus (Ascenzi and Gantt 1999;Tanaka et al 1999;Folco et al 2003). To determine the subcellular localization of MaHIS1 protein, the coding region of MaHIS1 was fused in-frame with the GFP gene, and the resulting constructs were then transfected into tobacco BY-2 protoplasts.…”
Section: Mahis1 Was a Nucleus-localized Proteinmentioning
confidence: 99%
“…Several H1 variants have been studied in both animal and plant organisms and most of them are considered tissue-or stage-specific, while others are accumulated during cell differentiation or in response to specific environmental signals (Jerzmanowski et al, 2000, Khochbin, 2001). For instance, in several liliaceous plants specific histone H1 variants appear during male meiosis (Ueda and Tanaka, 1995), other variants expressed during water deficit have been identified in several monocots and dicots (Scippa et al, 2004) whereas a specific H1 variant has been found to localize in nucleoli of higher plant cells (Tanaka et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although linker histones have been studied in several plant species (Ivanchenko et al, 1987, Srebreva et al, 1989, Tanaka et al, 1999, Jerzmanowski et al, 2000, Scippa et al, 2004, little is known about their spacial distribution during plant cell differentiation and dedifferentiation, processes that involve several alterations in chromatin structure and function. Even less is known about the effect of exogenous applied hormones on linker histone distribution, although there is evidence about alterations in histone H1 patterns after hormone treatment of animal cells (Wurtz, 1985).…”
Section: Introductionmentioning
confidence: 99%